2009
DOI: 10.1364/oe.18.000165
|View full text |Cite
|
Sign up to set email alerts
|

Direct near-field optical imaging of plasmonic resonances in metal nanoparticle pairs

Abstract: In this paper we investigate the near-field optical behavior of plasmon coupling in gold nanoparticle pairs. In particular, by performing series measurements through a fiber-collection mode near-field scanning optical microscope (NSOM), we directly observed the localized electromagnetic (EM) field distribution between two nanospheres is sensitively depended on the incident polarization and interparticle distance. The qualitative near-field observation and quantitative analysis facilitate more understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In this work, our aim is to directly observe the electromagnetic field distribution using a scanning near-field optical microscope (SNOM). Recently, many SNOM experiments have been performed on isolated or coupled nanostructures, [17][18][19][20] but only very few studies have been achieved on arrays. Salerno et al 21 and Salomon et al 22 observed the localization of light on an array of gold nanoparticles with a SNOM, but the structures were separated from each other by one micrometer, which makes them almost isolated from each other.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, our aim is to directly observe the electromagnetic field distribution using a scanning near-field optical microscope (SNOM). Recently, many SNOM experiments have been performed on isolated or coupled nanostructures, [17][18][19][20] but only very few studies have been achieved on arrays. Salerno et al 21 and Salomon et al 22 observed the localization of light on an array of gold nanoparticles with a SNOM, but the structures were separated from each other by one micrometer, which makes them almost isolated from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, only resonant field modes extend far and strongly enough into space to allow sufficient probe-sample separation. [26][27][28][29] On the plus side, SNOM readily offers spectroscopic capabilities, 30-34 the discrimination of two orthogonal polarization states [35][36][37] and time-resolved measurements. 38 With a careful preparation and independent characterization of the detecting probe it might become feasible to study unknown samples.…”
Section: Nearfield Optical Techniquesmentioning
confidence: 99%
“…(2) Means of writing the input and reading the output in the nanoscale are experimentally established. 23,31,32 (3) The entirely classical operation implies that creation and maintenance of entanglement are not necessary. (4) Metal nanoparticle can be prepared in large arrays in a controllable fashion.…”
Section: ∂Hmentioning
confidence: 99%